IMPACT OF IRON LEVELS ON EMBRYO QUALITY IN IVF: A QUANTITATIVE AND QUALITATIVE ANALYSIS - Zoitova Nilufar Mamurjanovna; Yuldasheva Dilchekhra Yusufkhanovna (Modern American Journals, 2025)
Iron deficiency is a prevalent condition among women of reproductive age and may negatively impact in vitro fertilization (IVF) outcomes. The role of iron in embryo quality and fertilization rates remains insufficiently studied.
Keywords: IVF, iron deficiency, ferritin, embryo quality, ovarian stimulation.